2021
DOI: 10.1007/s00068-021-01804-y
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of out-of-hours hip fracture surgery: insights from a retrospective nationwide study

Abstract: Purpose The study aimed to investigate the association between out-of-hours surgery and postoperative mortality in hip fracture patients. Furthermore, internal fixation and arthroplasty were compared to determine if a difference could be observed in patients operated with these techniques at different times during the day. Methods All patients above 18 of age years in Sweden who underwent hip fracture surgery between 2008 and 2017 were eligible for inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Logistic regression (LR) models were constructed with 30-day, 90-day, and 1-year postoperative mortality as the response variables [ 31 , 32 ]. The variables that were included as potential predictors were age, sex, ASA classification, type of surgery, type of fracture, out-of-hours surgery, time to surgery, ongoing beta-blocker therapy, CCI, RCRI, comorbidities including dementia, arrhythmia, hypertension, previous myocardial infarctions, congestive heart failure, cerebrovascular disease, chronic obstructive pulmonary disease (COPD), connective tissue diseases, diabetes mellitus, peptic ulcer disease, liver disease, hemiplegia, chronic kidney disease, local cancer, and metastatic carcinoma, as well as measurements of frailty [ 5 , 7 , 36 , 39 42 , 44 48 ]. Out-of-hours surgery was defined as surgery initiated between 17:00 and 8:00 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression (LR) models were constructed with 30-day, 90-day, and 1-year postoperative mortality as the response variables [ 31 , 32 ]. The variables that were included as potential predictors were age, sex, ASA classification, type of surgery, type of fracture, out-of-hours surgery, time to surgery, ongoing beta-blocker therapy, CCI, RCRI, comorbidities including dementia, arrhythmia, hypertension, previous myocardial infarctions, congestive heart failure, cerebrovascular disease, chronic obstructive pulmonary disease (COPD), connective tissue diseases, diabetes mellitus, peptic ulcer disease, liver disease, hemiplegia, chronic kidney disease, local cancer, and metastatic carcinoma, as well as measurements of frailty [ 5 , 7 , 36 , 39 42 , 44 48 ]. Out-of-hours surgery was defined as surgery initiated between 17:00 and 8:00 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]22 In addition, a recent study found that hip fracture repair occurring during "out-of-hours" (17:00-08:00) was associated with a 5% increase in 30-and 90-day mortality risk compared with "on-hour" (08:00-17:00). 23 We recognize that measuring in-hospital mortality is a distinctly different assessment than measuring 30-and 90-day postoperative mortality rates associated with hip fracture care. In-hospital mortality, which was looked at in our study, represents only a limited sample of patients experiencing mortality after hip fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, subgroup analyses were performed by repeating the regression analyses with specific subgroups of patients who were deemed to potentially be at a higher risk of suffering adverse events as a result of the choice of anesthesiological method used. These subgroups were selected since prior studies have observed an association between them and postoperative outcomes; they consisted of patients who underwent internal fixation or arthroplasty, had an extended surgical duration (surgical duration >100 min), had a reduced surgical fitness (ASA classification ≥3), had an elevated RCRI (RCRI ≥2), had an increased comorbidity burden (CCI ≥7), had a diagnosis of dementia prior to surgery, underwent surgery out-of-hours (17:00-08:00), and geriatric patients (aged ≥65 years) 5 18–22 24 25 31 32. An extended surgical duration was defined as any operation that lasted >100 min, as this was the 90th percentile for all operations in this dataset.…”
Section: Methodsmentioning
confidence: 99%
“…5 14 18 19 Furthermore, several other risk factors have been associated with an increased risk of adverse postoperative outcomes. [20][21][22][23][24][25] However, the latest meta-analyses have not conducted any subgroup analyses taking into account these different risk factors. Therefore, the aim of the current study was to evaluate the association between mode of anesthesia and postoperative morbidity as well as mortality within a general hip fracture population as well as within specific subgroups.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation